Mycotoxin contamination in feeds and feed materials in China in year 2020 - Li, Anping; Hao, Wei; Guan, Shu; Wang, Jinyong; An, Gang (Frontiers in Veterinary Science, 2022)
A survey of mycotoxin contamination in feed commodities in China was performed and the regional differences of mycotoxin contamination in new season corn was assessed during January 2020 to November 2020 in this research. 1610 samples were analyzed for the major mycotoxins, namely aflatoxins, zearalenone (ZEN), trichothecenes type B, fumonisins (FUM), fusariotoxin T-2 (T-2) and ochratoxin A (OTA) using methods of liquid chromatography - tandem mass spectrometry and enzyme linked immunosorbent assay. Generally, aflatoxins occurred in 16% of all samples, and ZEN, trichothecenes type B and FUM were more prevalent with positive rates of 47%, 72% and 63%, respectively. T2 and OTA were rarely detected. In new season corn, samples were also seriously contaminated with ZEN, trichothecenes type B, and FUM at positive rates of 47%, 76%, and 79%, respectively, and their averages of positives were 112 μg/kg, 735 μg/kg, and 3811 μg/kg, respectively. The patterns of mycotoxin occurrence showed distinct regional trends in new season corn samples. Samples from Shandong province were highly contaminated with FUM, while special attention should be paid to aflatoxins in Anhui and Jiangsu provinces of East China. The contents of trichothecenes type B and ZEN from northern to southern provinces showed downward trends. In new season corm, co-occurrence of mycotoxins was widespread, and combinations of ZEN, trichothecenes type B, and FUM were frequently observed in this study. Trichothecenes type B and ZEN concentrations showed a positive correlation coefficient of 0.294, suggesting that toxicological interactions of these toxins deserve attention.